2005
DOI: 10.1074/jbc.m411989200
|View full text |Cite
|
Sign up to set email alerts
|

The Antineoplastic Lectin of the Common Edible Mushroom (Agaricus bisporus) Has Two Binding Sites, Each Specific for a Different Configuration at a Single Epimeric Hydroxyl

Abstract: The lectin from the common mushroom Agaricus bisporus, the most popular edible species in Western countries, has potent antiproliferative effects on human epithelial cancer cells, without any apparent cytotoxicity. This property confers to it an important therapeutic potential as an antineoplastic agent. The three-dimensional structure of the lectin was determined by x-ray diffraction. The protein is a tetramer with 222 symmetry, and each monomer presents a novel fold with two ␤ sheets connected by a helix-loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
88
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 57 publications
0
88
0
Order By: Relevance
“…It was suggested that the archetypal actinoporin fold is used for specific binding to various molecules at the plasma membrane surface (Kristan et al 2009). Characterized representatives of the actinoporin-type mushroom lectin family include XCL, ABL (ABA), SRL, and BEL from the basidiomycetes Xerocomus (Boletus) chrysenteron, Agaricus bisporus, Sclerotium (Athelia) rolfsii, and B. edulis (Birck et al 2004;Bovi et al 2011;Carrizo et al 2005;Leonidas et al 2007) and AOL 2 and TAP1 from the ascomycetes Arthrobotrys oligospora and Sordaria macrospora (Nowrousian and Cebula 2005;Rosen et al 1996b). These representatives of basidiomycetes share 53 to 82 % sequence identity (67 to 89 % similarity), while AOL 2 is approximately 45 % identical (62 % similar) to them and TAP1 only 34 % identical (50 % similar).…”
Section: Actinoporin-type Lectinsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that the archetypal actinoporin fold is used for specific binding to various molecules at the plasma membrane surface (Kristan et al 2009). Characterized representatives of the actinoporin-type mushroom lectin family include XCL, ABL (ABA), SRL, and BEL from the basidiomycetes Xerocomus (Boletus) chrysenteron, Agaricus bisporus, Sclerotium (Athelia) rolfsii, and B. edulis (Birck et al 2004;Bovi et al 2011;Carrizo et al 2005;Leonidas et al 2007) and AOL 2 and TAP1 from the ascomycetes Arthrobotrys oligospora and Sordaria macrospora (Nowrousian and Cebula 2005;Rosen et al 1996b). These representatives of basidiomycetes share 53 to 82 % sequence identity (67 to 89 % similarity), while AOL 2 is approximately 45 % identical (62 % similar) to them and TAP1 only 34 % identical (50 % similar).…”
Section: Actinoporin-type Lectinsmentioning
confidence: 99%
“…1). SRL was shown to be a dimer but can, from a structural point of view, form similar tetramers as other representatives (Birck et al 2004;Bovi et al 2011;Carrizo et al 2005;Leonidas et al 2007).…”
Section: Actinoporin-type Lectinsmentioning
confidence: 99%
“…Some lectins recognize exposed T-antigen glycosides only (e.g. peanut agglutinin and ABL) (59,68); however, some lectins can recognize cryptic T-antigens masked by modifying sugar units such as sialic acids. The binding specificity of GL-BP is higher compared with lectins; it recognizes only the exposed nonreducing GNB or LNB portion without any modifications, and the affinity is stronger compared with lectins.…”
Section: Analysis Of Ligand Specificity By Itc-mentioning
confidence: 99%
“…The parameters of LNB and T-antigen (Gal␤1-3GalNAc-␣-O-Ser) bound to the Agaricus bisporus lectin (ABL) (59) are shown in the Table 3. The conformation of LNT bound to GL-BP is similar to that of LNT in solution.…”
Section: Analysis Of Ligand Specificity By Itc-mentioning
confidence: 99%
See 1 more Smart Citation